IMPLIKASI INTEGRASI PENGEMBANGAN SOFTSKILL, DAN AUGMENTED REALITY PADA PENDIDIKAN DASAR DI ERA DIGITAL - Rozi, Fahrur; Fauzi, KMS. M. Amin (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2024)
Improved Softskill Development and Augmented Reality In addition to focusing on mastery of academic material, basic education increasingly emphasizes the development of soft skills or soft skills that are essential for success in this digital era. Universitas Negeri Medan (UNIMED) as one of the LPTK that produces teachers since 2011 has set a strategy towards 2025 by launching the development of its role in producing quality teachers. One of the directions developed is to make UNIMED as "The character building university" by developing a learning revolution that seeks to develop soft skills in learning. Based on the search conducted through ethnic groups in North Sumatra, 15 attributes of the most relevant soft skills were formulated, including: (1) religious, (2) discipline, (3) visionary, (4) cooperation, (5) leadership and organization, (6) adaptable/ flexible, (7) tolerant/ friendly, (8) oral communication, (9) written communication, (10) problem solving, (11) confidence, (12) caring, (13) serving, (14) honesty, and (15) responsibility at work. Augmented Reality in particular has shown its great potential to enhance STEM (Science, Technology, Engineering, and Mathematics) education. Virtual laboratories, and to replicate real-world scenarios and visualize complicated scientific phenomena in Physics, Chemistry, Biology, Mathematics, and Engineering Education.